2005
DOI: 10.1021/es048044l
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Oxytetracycline to Iron Oxides and Iron Oxide-Rich Soils

Abstract: The sorption interactions of oxytetracycline with goethite, hematite, and two iron oxide-rich soils were investigated using batch sorption experiments. Oxytetracycline sorption coefficients for goethite and hematite increased with pH to maximum values at pH approximately 8. The sorption edge shape and desorption treatments were consistent with a surface complexation mechanism and could be described by the interaction of divalent anion species with the oxide surface. Oxytetracycline sorption to Georgeville and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
172
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(192 citation statements)
references
References 41 publications
14
172
2
4
Order By: Relevance
“…No antibiotics from tetracyclines were detected in the rivers and WWTP effluents, probably due to their strong binding capacity to particulate matters and interaction with cations. [32,33] Thus only these detected antibiotics were discussed in the following section. No antibiotics were detected in the samples from site S0 (Liuxi Reservoir), which was used as the control and also used in the spiking tests.…”
Section: Antibiotics In Pearl Riversmentioning
confidence: 99%
“…No antibiotics from tetracyclines were detected in the rivers and WWTP effluents, probably due to their strong binding capacity to particulate matters and interaction with cations. [32,33] Thus only these detected antibiotics were discussed in the following section. No antibiotics were detected in the samples from site S0 (Liuxi Reservoir), which was used as the control and also used in the spiking tests.…”
Section: Antibiotics In Pearl Riversmentioning
confidence: 99%
“…S1b), for pH values between 3.0 and 5.0, the molar fraction of zwitterionic OTC (H2OTC) increases from 0.5 to nearly 1.0. Figueroa and Mackay [36] reported that the expected initial decrease in the concentrations of OTC and DOC with increasing pH after the iron salt addition step is a consequence of the interaction between ferrous hydrous oxides and deprotonated OTC species. Taking into consideration Eq.…”
Section: Conventional Fe 2+ /H2o2/uv-vis Reactionmentioning
confidence: 99%
“…Como resultado, verificou-se que as espécies aniônicas do fármaco apresentaram tendência superior, em relação às formas zwitteriônicas, à complexação com a superfície neutra do óxido. 66 Em contrapartida, no modelo de sorção desenvolvido por Sassman e Lee, 56 os K d calculados para a TC, OTC e CTC foram maiores para as espécies catiônicas, considerando a sorção dos fármacos nos sítios negativos do solo.…”
Section: +unclassified
“…64,69 Entretanto, em outras situações, o modelo de Langmuir (Equação 3) mostrou-se mais adequado. 61,66,76 Para o melhor entendimento destes modelos pode ser consultado o trabalho publicado por Travis e Etnier. Os estudos de dessorção são realizados com o objetivo de investigar se a retenção do contaminante no solo ocorre de forma reversível ou não.…”
Section: Determinação Dos Coeficientes De Sorção E Dessorção De Contaunclassified